Gender Disparities in Engineering and Technical Education in India: A Review - Parmar, Sargam (International Journal of Psychosocial Rehabilitation, 2020)
Education plays a crucial role in the socio-economic development of a country. It contributes significantly to human development by reducing poverty, ignorance, and social exclusion. Ensuring equitable access to education for all sections of society, particularly marginalized groups, is essential for inclusive growth. After elementary and secondary education, technical education becomes a key driver of skill development, employability, and national productivity. In India, women constitute nearly half of the total population; however, their enrolment in technical education remains significantly lower than that of men. This persistent gender gap in technical education is a matter of serious concern and reflects broader socio-economic and cultural constraints. The present study analyzes the trends in female enrolment in diploma and degree-level engineering education in India using secondary data from national sources. The paper also examines branch-wise gender participation and identifies key factors influencing disciplinary choices. Based on the findings, the study proposes policy-oriented suggestions to reduce the gender gap and promote women’s participation in higher technical education.